Antidumping dan Countervailing Duty dalam Sengketa Perdagangan Udang Indonesia-Amerika Serikat - Aji Baskoro (Cendekia Niaga, 2026)
The shrimp trade dispute between Indonesia and the United States over the past two decades reflects the complex dynamics surrounding the application of antidumping (AD) and countervailing duty (CVD) measures within the multilateral trading system. This study aims to analyze the implementation of these trade remedy instruments, assess their consistency with World Trade Organization (WTO) legal principles, and formulate policy implications for strengthening Indonesia’s response to trade remedies. The research employs a normative juridical approach, complemented by an analysis of trade data and fisheries sector policies, in order to provide a comprehensive synthesis of legal and economic dimensions. The findings indicate that the imposition of AD and CVD measures by the United States on Indonesian shrimp exports has been recurrent, primarily through investigations and annual administrative reviews. Such practices have generated tariff uncertainty and exerted pressure on Indonesia’s export price competitiveness. Although AD and CVD instruments are recognized under the WTO framework as legitimate tools to address unfair trade practices, their application in this case raises concerns regarding compliance with core WTO principles, including non-discrimination, transparency, due process, and the methodologies used in determining dumping margins and actionable subsidies. The more pronounced fluctuation in export value compared to export volume suggests that the primary impact of these measures lies in reduced profit margins rather than diminished market access. The study further reveals that Indonesia’s defense strategies, through active participation in investigations, trade diplomacy, and WTO-based legal argumentation, have succeeded in reducing dumping margins in certain review periods. However, these efforts remain largely reactive. Structural challenges such as limited data capacity, institutional coordination, and litigation financing require substantial improvement. Policy implications highlight the urgency of developing an early warning system, harmonizing domestic subsidy policies with WTO rules, enhancing exporters’ technical and legal capacity, and diversifying export markets. A comprehensive and preventive approach is essential to strengthen national trade resilience and enhance Indonesia’s bargaining position amid rising global protectionism.